CAMPUR KODE DAN ALIH KODE DALAM NOVEL CINTA TERAKHIR SANG SULTAN KARYA SUNARDIAN WIRODONO - Lutfia Nur Oktaviani; Patriantoro Patriantoro; Agus Syahrani (Universitas Tanjungpura, 2019)
AbstractThe research method used is descriptive qualitative research. The source of data is the novel Cinta terakhir Sang Sultan by Sunardian Wirodono. The research data is words and sentences in the form of code mixing and code switching. The technique of data collection uses documentary. The tools of data collection are a laptop and data cards. The analysis results indicate that there are 78 data being analyzed in the novel Cinta terakhir Sang Sultan by Sunardian Wirodono. The occurrences of code mixing of Javanese are 56 data, while the occurrences of code mixing of Dutch and English are 19 data. The code switching has 3 data. The word level of code mixing has 33 data, while the phrase level has 12 data, clause level with 6 data, idiom level with 5 data, baster level with 5 data, reduplication level with 1 data and external code switching with 3 data. The background of code mixing is 19 data, while the background of code switching is 3 data. The factors that influence the occurrence of code mixing are 12 data, while the factors of code switching are 3 data. Keywords: Descriptive, Code Mixing, Code Switching